Medical attention injury rates in US women rugby-7s - Lopez Jr, V. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: There is a lack of injury data on women`s rugby, and less on the Olympic format of Rugby-7s among the amateur playing population (Lopez et al., 2012; Ma et al., 2016). The aim was to determine medical attention (no time-loss) injury incidence in U.S. women`s Rugby-7s.